Contratos coligados e a repercussão de suas vicissitudes perante as partes e terceiros - Veiga, Edna Teixeira (2020)
The business reality led to linked contracts, which refer to two or more separated contracts interrelated by a common objective or by their ancillary nature. Linked contracts have autonomous structures and can be concluded by either the same or different parties. The execution of linked contracts between different parties poses greater challenges in view of the principle of relativity of contracts’ effects (Doctrine of Privity of Contracts). The present study aims to define and classify linked contracts, in order to better understand the theory that involves them. It will approach the legal effects of contracts – both internally (between parties) and externally (to third parties) –, through the analysis of the relativity principle, the enforceability of the contractual effects to third parties and the concepts of party and third party. The research will present the main angles of interpretation of legal businesses, a premise for identifying linked contracts and analyzing its effects. It will address the obligation as a dynamic process, which guides the cooperation between the parties and the fulfillment of the lateral duties of conduct in good faith. In the present investigation, this perspective is substantiated by the practical importance that the cooperation and the lateral duties assume in linked contracts, which may be imposed on third parties with regard to a given contract, part of a chain. Thus, after an analysis of the main characteristics and issues applicable to the linked contracts, some legal issues on their relationship will be pointed out, mainly on their impact regarding nullity, ineffectiveness and default